PROBLEMATIKA PENERAPAN PERINSIP SUSTAINABLE DEVELOPMENT DALAM PENGELOLAAN LINGKUNGAN HIDUP DAN IMPLIKASINYA TERHADAP PEMENUHAN HAM - Suardi Suardi (Fakultas Hukum Universitas Muhammadiyah Palu, 2018)
The principle of Sustainable Development in the management of the environment is a principle born of the response to serious environmental damage and give effect to the survival of human life in Planet Earth, the more damaged the environment is the higher the threat to humanity itself. Therefore, development is a peroses fulfillment of human needs in rebound supported by the capability of the optimal environmental capacity to human needs. Thus throughout the environment choose the high carrying capacity so the stability of human life the better also the opposite also the higher the needs of humans in life must be supported with the carrying capacity of a good environment that can serve as a life suporting system. On the implementation of the principle of Sustainable Development has experienced complex problems in carrying out the balance of the needs of human life and the environment itself consequently the environmental damage becomes severe and as if not able to overcome, humans assume that the available natural resources are materials that must be exploited for the sake of fulfillment consumptive human needs.. Keyword : The Implementation of the Province of Sustainable Development, Human Rights.